A Population-based Study of Visual Impairment Among Pre-school Children in Beijing: The Beijing Study of Visual Impairment in Children - Lu, Qing; Zheng, Yuanyuan; Sun, Baochen; Cui, Tongtong; Congdon, Nathan; Hu, Ailian; Chen, Jianhua; Shi, Jiliang (American journal of ophthalmology, 2009)
To evaluate the prevalence and causes of visual impairment among Chinese children aged 3 to 6 years in Beijing. Population-based prevalence survey. Presenting and pinhole visual acuity were tested using picture optotypes or, in children with pinhole vision < 6/18, a Snellen tumbling E chart. Comprehensive eye examinations and cycloplegic refraction were carried out for children with pinhole vision < 6/18 in the better-seeing eye. All examinations were completed on 17,699 children aged 3 to 6 years (95.3% of sample). Subjects with bilateral correctable low vision (presenting vision < 6/18 correctable to ≥ 6/18) numbered 57 (0.322%; 95% confidence interval [CI], 0.237% to 0.403%), while 14 (0.079%; 95% CI, 0.038% to 0.120%) had bilateral uncorrectable low vision (best-corrected vision of < 6/18 and ≥ 3/60), and 5 subjects (0.028%; 95% CI, 0.004% to 0.054%) were bilaterally blind (best-corrected acuity < 3/60). The etiology of 76 cases of visual impairment included: refractive error in 57 children (75%), hereditary factors (microphthalmos, congenital cataract, congenital motor nystagmus, albinism, and optic nerve disease) in 13 children (17.1 %), amblyopia in 3 children (3.95%), and cortical blindness in 1 child (1.3%). The cause of visual impairment could not be established in 2 (2.63%) children. The prevalence of visual impairment did not differ by gender, but correctable low vision was significantly ( P < .0001) more common among urban as compared with rural children. The leading causes of visual impairment among Chinese preschool-aged children are refractive error and hereditary eye diseases. A higher prevalence of refractive error is already present among urban as compared with rural children in this preschool population.